PENYULUHAN HIPERTENSI SEBAGAI UPAYA PENINGKATAN PENGETAHUAN MASYARAKAT RW 02 KELURAHAN PONDOK RANJI, TANGERANG SELATAN - Fauziah, Munaya; Amin, Khairil; Rahmadita, Ananda Kezia Nashra; Noviar, Andika Surya; Winnia, Adinda Jilan Hikaru; Hafidzah, Shila Najla; Ramadhani, Lutfiah Kurnia Putri; Pratama, Zahra Diva (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
Hypertension is a non-communicable disease with a high prevalence in Indonesia and carries the risk of serious complications. Low public knowledge is one of the causes of hypertension that causes high incidence rates. The objective of this activity is to increase the knowledge and awareness of the community in RW 02, Pondok Ranji Village, about hypertension through interactive education and promotion of a healthy lifestyle. The activity was carried out on May 31, 2025, in the form of healthy exercise, interactive counseling, pre-tests and post-tests, and the distribution of healthy juices. Assessment was carried out using quantitative analysis of the pre-test and post-test and participatory observation. Results: There was an increase in the average knowledge score from 64.6 to 86.8 (p = 0.000). All participants (n = 30) showed an increase in the good knowledge category. The input-process-output evaluation showed the achievement of the activity target. The conclusion of this activity is that community education has proven effective in increasing public knowledge about hypertension. The strategy of interactive needs to be maintained in community health promotion.